Abbott Elementary. The complete first season [videorecording (DVD)] - Brunson, Quinta; Brunson, Quinta; Williams, Tyler James, 1992-; James, Janelle; Walter, Lisa Ann, 1963- (Warner Bros. Entertainment, 2022)
In this workplace comedy from writer/executive producer/star Quinta Brunson and executive producers Justin Halpern & Patrick Schumacker, a group of teachers is brought together in a Philadelphia public school, because they love teaching. Though outnumbered and underfunded, they love what they do even if they don't love the school district's less-than-stellar attitude toward educating children.